HUBUNGAN FAKTOR RESIKO DENGAN TERJADINYA NYERI PUNGGUNG BAWAH (LOW BACK PAIN) PADA TENAGA KERJA BONGKAR MUAT (TKBM) DI PELABUHAN BELAWAN MEDAN TAHUN 2015 - Nurzannah -; makmur sinaga; umi salmah (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT More than 70% humans had ever experience Low Back Pain (LBP) at the age of 35 – 55 years old. Some risk factors with LBP incidents is at the age over 35 years old, smoker, 5- 10 years work time, work position, overweight ans musculoskeletal disorder sufferer family history, Body Mass Index (BMI), height, exercise routine, and work time. The purpose of this research is to defind personal factors (age, IMT, work time, work periode, smoking habit, exercise routine) and work factors (work load, work posture) with the incidents of Low Back Pain with loading and unloading worker (TKBM) at Belawan harbor. This research type is case control design with retrospektif characteristic. Population in this research was 460 people with sample taken  systematically random sampling that was 64 people. the data analysis in univariat and bivariat manner. The research result showing at the age distributing (p=0.021 ; OR = 0.29), IMT (p = 0.613 ; OR = 0.312), work time (p = 0.019 ; OR = 0.247), Work periode (p = 1.000 ; OR = 1.552), smoking (p = 1.000 ; OR = 0.724), exercise (p = 0.021; OR = 0.259), work load (p = 0.042 ; OR = 0.304) , work posture (p = 0.039 ; OR = 0.294). It is suggested to TKBM to exercising or warming up before doing physical activity/work. To the TKBM Belawan harnor  primer cooperative suggested to give promotion about LBP prevention by paying attention to the rest time, workplace, liftload, assist used, also protector tools for TKBM Belawan harbor.